Emerging role of extracellular vesicles and exogenous stimuli in molecular mechanisms of peripheral nerve regeneration - Izhiman, Yara; Esfandiari, Leyla (Frontiers in Cellular Neuroscience, 2024)
Peripheral nerve injuries lead to significant morbidity and adversely affect quality of life. The peripheral nervous system harbors the unique trait of autonomous regeneration; however, achieving successful regeneration remains uncertain. Research continues to augment and expedite successful peripheral nerve recovery, offering promising strategies for promoting peripheral nerve regeneration (PNR). These include leveraging extracellular vesicle (EV) communication and harnessing cellular activation through electrical and mechanical stimulation. Small extracellular vesicles (sEVs), 30-150 nm in diameter, play a pivotal role in regulating intercellular communication within the regenerative cascade, specifically among nerve cells, Schwann cells, macrophages, and fibroblasts. Furthermore, the utilization of exogenous stimuli, including electrical stimulation (ES), ultrasound stimulation (US), and extracorporeal shock wave therapy (ESWT), offers remarkable advantages in accelerating and augmenting PNR. Moreover, the application of mechanical and electrical stimuli can potentially affect the biogenesis and secretion of sEVs, consequently leading to potential improvements in PNR. In this review article, we comprehensively delve into the intricacies of cell-to-cell communication facilitated by sEVs and the key regulatory signaling pathways governing PNR. Additionally, we investigated the broad-ranging impacts of ES, US, and ESWT on PNR.